Settings open accessreview modes and approaches of groundwater governance: a survey of lessons learned from selected cases across the globe - Robert G. Varady, Adriana A. Zuniga-Teran, Andrea K. Gerlak and Sharon B. Megdal (My University, 2016)
The crucial role of groundwater and the centrality of water governance in accommodating growing water demands sustainably are becoming well recognized. We review 10 case studies of groundwater governance&mdashrepresenting diverse global regions and local contexts&mdashfrom the perspective of four well-established elements: (1) institutional setting (2) availability and access to information and science (3) robustness of civil society and (4) economic and regulatory frameworks. For institutional setting, we find that governing is often a thankless task that paradoxically requires popularity legislation does not always translate to implementation conflict resolution is central to governance and funding is critical for governance. In terms of information access, we see: a need for research for natural systems, social systems, and institutions trust as an essential element in research and that urbanized landscapes are critical components of groundwater governance. Looking at civil society robustness, we observe that equity is an essential element for governance community-based governance requires intention and leaders can play a powerful role in uniting stakeholders. As for frameworks, the cases suggest that economic incentives sometimes yield unintended results &ldquoindirect&rdquo management should be used cautiously and economic incentives&rsquo effectiveness depends on the system employed. Collectively, the lessons speak to the need for shared governance capacities on the part of governments at multiple levels and civil society actors.
Keywords: groundwater governance, water stakeholder participation, equity, water security, case studies